MANAGEMENT IN CLEFT LIP AND PALATE SURGERY : A SYSTEMATIC REVIEW - Lasma Azaria, Yohana (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Cleft lip and palate, sometimes referred to as labioplatoschizis, is one of the most common types of congenital disorders found in Indonesian babies. A person is said to have cleft lip and cleft palate if they have a cleft in their upper lip as well as a cleft in the roof of their mouth, which results in a direct connection between their nostril and mouth. This condition is also known as cleft lip and palate syndrome. This disorder could be hereditary or it could be acquired. Both the cleft lip and the cleft palate can happen on their own (just the cleft lip or just the cleft palate), or they can happen simultaneously. (cleft lip and cleft palate). The embryological process of facial structure creation is integrally related to the pathophysiology of orofacial clefts, which can occur on the lip (labioschisis), palate (palatoschisis), or both. Orofacial clefts can be divided into three categories: labioschisis, palatoschisis, and both. (also known as labiopalatoschisis). Clefts of the lip or palate are a possibility. Cleft lips are caused by the failure of the maxillary bone to fuse with the bones of the palate and the nasal passageway. No matter what kind of tissue is involved, the technique for surgical removal is the same. The surgeon will work to restore the patient's normal anatomy and physiology and will also make an effort to rehabilitate their mental health. There is an increased likelihood of death or morbidity in those who have cleft lips, palates, or labiopalatoschisis. Syndromes associated with cleft palate are associated with an increased risk of death and morbidity. Morbidity is increased when there are complications.